Study of the Hydrocarbon-oxidizing Activity of Bacteria of the Genera Pseudomonas and Rhodococcus; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Astashkina A. P. Anna Pavlovna; Bakibaev A. A. Abdigali Abdimanapovich; Plotnikov E. V. Evgeny Vladimirovich; Kolbysheva Yu. V. Yuliya Vladimirovna; Mukashev A. B. (2015, 2015)
Title screen